DRUG-ADMINISTERING PERSONS' EXPOSURE TO ORAL ANTICANCER DRUGS TO BE ADMINISTERED THROUGH A TUBE - Murakami, Masahiro; Katsuragi, Satoko; Ohno, Masako; Shigematsu, Makoto; Kishi, Ayumi; Zamami, Yoshito; Komada, Fusao; Kurata, Naomi; Amano, Manabu (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of this study was to quantitatively evaluate anticancer drug exposure of non-health care professionals who administer drugs through a tube employing a method devised by us. Methods: The subjects were 30 general volunteers aged 22-84 years. They wore gloves and administered Indian ink, simulating an anticancer drug, to a multipurpose adult human-type patient care simulator through a tube using 5 types of syringe, and the area stained with Indian ink was measured. Results: When comparing the number of pixels among the syringes regardless of age, Syringe B showed the lowest number (11.8Â±3.1 cm2), and there was a significant difference between Syringes B and E. Furthermore, we compared the total number of pixels in each age group regardless of the type of syringe. In the 20-year-old group, it was the lowest (10.9Â±2.3 cm2) showing significant differences in comparison with the other groups. When Syringe B was used, the number of pixels was markedly lower than on adopting the other syringes. Conclusion: It was clarified that the level of exposure to anticancer drugs markedly varies depending on the type of syringe and age. It was also clarified that the method to evaluate exposure to anticancer drugs using Indian ink devised by us is simple and useful. Keywords: Oral anticancer drugs, Simple suspension method, Drug-administering persons' exposure.